Concrete Bridge Deterioration Caused by De-Icing Salts in High Traffic Volume Road Environment in Latvia - Kristaps Gode; Ainars Paeglitis (The Baltic Journal of Road and Bridge Engineering)
Design for durability of road infrastructures is becoming increasingly important in view of its large impact on economics. Reinforcement corrosion is the most common cause of concrete deterioration of bridge structures in Latvia. The ingress of chlorides is often considered to be the major threat to durability of concrete structures. During the winter season de-icing salts are spread out on roads to avoid formation of ice and ensure the anti-sliding properties of the road surface. The melting water mixes with de-icing salt are splashed and sprayed on reinforced concrete pier structures by passing vehicles. Absorbed water with chloride ions initiates and accelerates the reinforcement corrosion process. This paper highlights the results of investing accumulation of chlorides in reinforced concrete bridge piers located near high traffic volume roads in Latvia. The chloride contents were determined on different surfaces of reinforced concrete piers. Environmental conditions were analysed and prediction of remaining service life for chloride induced reinforcement corrosion was performed.